Recent developments in Asian economics - Barnett, William A.; Sergi, Bruno S. (International symposia in economic theory and econometrics, 2021)
This volume of the 'International Symposia in Economic Theory and Econometrics' explores the latest economic and financial developments in Asia. Chapters cover a range of topics such as the online market's impact on Indonesia's social welfare system, the influence of organizational culture on the triple bottom line performance of large manufacturing companies in the Philippines, and the impact of economic policy uncertainty on foreign direct investment inflows in India. These peer-reviewed papers touch on a variety of timely, interdisciplinary subjects such as sustainability and the effects of public policy. 'Recent Developments in Asian Economics' also includes empirical studies in financial economics and public governance. For example, one chapter considers the consumption and satisfaction of Chinese rural residents, while another empirically studies the effects of sharia disclosure and sharia supervisory boards on Islamic banks' soundness. The papers in this volume have been compiled from four conferences in Asia and Australia, including the SIBR 2020 Sydney Conference on Interdisciplinary Business and Economic Research, which was held in Sydney, Australia; the 5th Indonesian Finance Association (IFA) Conference held in Manado, Indonesia in 2019; the 1st International Doctoral Colloquium on Business and Economics in Surakarta, Indonesia; and the 5th Sebelas Maret International Conference on Business, Economics and Social Sciences held in 2018 in Bali, Indonesia. Together, ISETE 28 is a crucial resource of current, cutting-edge research for any scholar of international finance and economics.